CA125 and HE4 levels in a Czech female population diagnosed with endometrial cancer in preoperative management - Presl, Jiri; Novotny, Zdenek; Topolcan, Ondrej; Vlasak, Pavel; Kucera, Radek; Fuchsova, Radka; Vrzalova, Jindra; Betincova, Lucie; Svobodova, Sarka (Anticancer research, 2014)
AIM: The aim of the present study was to compare the use of cancer antigen 125 (CA125) and human epididymis protein 4 (HE4) biomarkers in patients with endometrial cancer for preoperative management and to particularly focus on relationship between CA125 and HE4 and disease stage in predicting myometrial invasion or intrauterine tumor spread. PATIENTS AND METHODS: Thirty-four patients diagnosed with endometrial cancer and 32 healthy controls were enrolled into the pilot study in the period between May 2012 and March 2013. Blood from all the females was collected and examined for CA125 and HE4. Based on standardized ultrasound examination, including gynecological examination, the clinical disease stage was determined. RESULTS: We found a significant difference (p<0.0001) for means of serum levels of HE4: females with endometrial cancer, 75.5 pmol/l, versus healthy females, 40.0 pmol/l. A non-significant statistical difference was found for mean serum CA125 levels (p=0.4442): females with endometrial cancer 19.0 IU/l, versus healthy females, 15 IU/l. A significant correlation with histopathological disease stage was found for both biomarkers (Spearman correlation). Sensitivity and specificity, and the related cut-off for HE4 suggest that HE4 would be a more appropriate biomarker for differential diagnosis between benign and malignant states. CONCLUSION: Based on our pilot study, we found that parallel examination of HE4 and CA125 may support endometrial ultrasound finding verification prior to biopsy. This study is ongoing and we expect that results on a larger population may enable HE4 measurement to be implemented in routine practice.
Keywords: senioři; CA-125 Antigen; Neoplasm Invasiveness; Endometrial cancer; senioři nad 80 let; Male; Prognosis; proteiny; Middle Aged; ROC Curve; mužské pohlaví; studie případů a kontrol; CA125; Adult; nádory endometria; ROC křivka; Endometrial Neoplasms; Follow-Up Studies; antigen CA-125; Biomarkers, Tumor; WAP Four-Disulfide Core Domain Protein 2; následné studie; HE4; Aged, 80 and over; Neoplasm Staging; ženské pohlaví; nádorové biomarkery; prognóza; Humans; pilotní projekty; invazivní růst nádoru; Proteins; lidé středního věku; tumor markers; Pilot Projects; staging nádorů; protein WFDC2; dospělí; Female; Aged; Preoperative Care; předoperační péče; lidé; Case-Control Studies